2017
DOI: 10.1080/10942912.2017.1288133
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bitter compounds from dried fruit of Ziziphus jujuba cv. Junzao

Abstract: Bitterness in dried jujube fruit can adversely influence its palatability and consumer acceptability. In the present investigation, sensory-guided fractionation with techniques of liquid-liquid extraction, macroporous resin separation, and LC-MS/QTof was applied to identify the bitter compounds in dried jujube fruit (Z. jujuba cv. junzao). The results showed that bitter substances can be successfully extracted from dried jujube fruit using ethanol followed by n-butanol solution. The extract could then be furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Nineteen phenolic compounds, including five flavanols (procyanidin B1, procyanidin B2, procyanidin B3, (−)-epicatechin and (+)-catechin), six phenolic acids (gallic acid, chlorogenic acid, caffeic acid, ferulic acid and cinnamic acid) and five flavonols (quercetin-3-galactoside, quercitrin-3-glucoside, quercetin-3-rutinose, quercetin-3-rhamnoside and quercetin) were well separated and quantified by HPLC. Similar types of phenolic compounds have been described previously in jujubes [ 11 , 18 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 76%
“…Nineteen phenolic compounds, including five flavanols (procyanidin B1, procyanidin B2, procyanidin B3, (−)-epicatechin and (+)-catechin), six phenolic acids (gallic acid, chlorogenic acid, caffeic acid, ferulic acid and cinnamic acid) and five flavonols (quercetin-3-galactoside, quercitrin-3-glucoside, quercetin-3-rutinose, quercetin-3-rhamnoside and quercetin) were well separated and quantified by HPLC. Similar types of phenolic compounds have been described previously in jujubes [ 11 , 18 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 76%
“…Previous studies have performed Ultra-High-Performance Liquid Chromatography (UPLC) analyses with species from the Ziziphus genus of the Rhamnaceae family, where some of these corroborate with the chemical composition found in the extracts herein, such as Ziziphus mauritiana (26,27), Ziziphus jujuba (28) and Ziziphus jujuba (29,30).…”
Section: Discussionsupporting
confidence: 67%
“…8 In our previous study, bitterness was also perceived in dried jujube fruit stored for 3 months at ambient temperature, and a series of phytochemicals and nitrogen compounds were tentatively identified from bitter fractions of the dried jujube fruit by LC-MS/MS. 9 Although there is little knowledge on bitterness formation during harvest, drying and storage of jujube fruit, a number of studies have indicated that bitterness could be perceived in jujube fruit and its products.…”
Section: Introductionmentioning
confidence: 99%